Oxidative Degradation of Amino Acids and Aminophosphonic Acids by 2, 2′‐Bipyridine Complexes of Copper(II). Issue 17 (19th May 2014) - Pap, József S.; El Bakkali‐Tahéri, Nadia; Fadel, Antoine; Góger, Szabina; Bogáth, Dóra; Molnár, Milán; Giorgi, Michel; Speier, Gábor; Simaan, A. Jalila; Kaizer, József
Abstract: Copper(II)–amino acid (AA) complexes that contain 2, 2′‐bipyridine (bpy) as supporting ligand were investigated. X‐ray structural analysis of three new bpy‐based complexes revealed a bidentate coordination of the AAs on the copper(II) centers similar to that proposed for the substrate on the iron(II) center of the 1‐aminocyclopropane‐1‐carboxylic acid oxidase (ACCO). Similar complexes with two aminophosphonic acids (APAs), 1‐aminocyclopropane‐1‐phosphonic acid (ACP) and (1‐amino‐1‐methyl)ethylphosphonic acid (AMEP), were also investigated, and the latter complex was structurally characterized. This structure reveals the bidentate coordination of α‐aminophosphonate on the copper(II) ion. The oxidation of the bound amino acids (AAs) and aminophosphonates (APAs), which model the reaction catalyzed by ACCO, was investigated. The complexes react with H2 O2 and give oxidation products that were identified by gas chromatography. Reduction of Cu II to Cu I was detected by UV/Vis spectroscopy upon reaction with H2 O2 or ascorbate. This reduction is proposed to be the initial step for the peroxide/copper activation prior to the oxidation of the AA and APA ligands by means of a radical mechanism. Abstract : The oxidation of bound amino acids or aminophosphonic acids by copper(II) complexes, which models the reaction catalyzed by the 1‐aminocyclopropane carboxylic acid oxidase, was investigated in the presence of hydrogen peroxide. A reaction mechanism that involves a Cu I intermediate is discussed.